Roles of BUMDes in Increasing Village Income and Community Sustainability - Prihartini, Intan; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Village-owned enterprises (BUMDes) play a crucial role in enhancing rural economic resilience in Indonesia. Specific Background:This study investigates the contributions of BUMDes Subur Makmur in Dukuhsari Village, Jabon District, to increasing Original Village Income (PADes). Knowledge Gap:Despite the potential of BUMDes, limited empirical evidence addresses the specific operational roles of BUMDes Subur Makmur in local economic development. Aims:This research aims to analyze the roles of BUMDes Subur Makmur as a facilitator, mediator, and motivator in enhancing PADes. Results:Findings reveal that BUMDes Subur Makmur effectively facilitates access to capital through savings and loans, mediates essential services like PPOB, and motivates community participation in waste management through its integrated program (TPST). Novelty: This study contributes to the literature by detailing the multidimensional roles of BUMDes in rural development. Implications: Strengthening BUMDes' operational capabilities is essential for maximizing their impact on local economies, highlighting the need for enhanced training and resources. Highlights: Role of BUMDes: Acts as a facilitator for local entrepreneurs by providing access to capital. Service Mediation: Enhances community access to essential utilities through integrated services like PPOB. Community Motivation: Encourages participation in sustainable practices via its integrated waste management program (TPST). Keywords: BUMDes, Original Village Income, Rural Development, Economic Resilience